1997
DOI: 10.1073/pnas.94.5.1657
|View full text |Cite
|
Sign up to set email alerts
|

A mixed-charge pair in human interleukin 4 dominates high-affinity interaction with the receptor α chain

Abstract: Human interleukin 4 (IL-4) binds to its

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
73
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 84 publications
(78 citation statements)
references
References 38 publications
5
73
0
Order By: Relevance
“…Similar electrostatic interactions have been described in the human GM-CSF-receptor complex (33,34) and the IL-4⅐IL-4 receptor ␣ chain complex (35). Arg 280 in the ␣-chain of the GM-CSF-R makes an electrostatic interaction with Asp 112 in the D helix of GM-CSF (33), whereas Glu 21 in the A helix probably interacts with Tyr 365 , His 367 , and Ile 368 of the ␤-common receptor chain (34).…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Similar electrostatic interactions have been described in the human GM-CSF-receptor complex (33,34) and the IL-4⅐IL-4 receptor ␣ chain complex (35). Arg 280 in the ␣-chain of the GM-CSF-R makes an electrostatic interaction with Asp 112 in the D helix of GM-CSF (33), whereas Glu 21 in the A helix probably interacts with Tyr 365 , His 367 , and Ile 368 of the ␤-common receptor chain (34).…”
Section: Discussionmentioning
confidence: 63%
“…Arg 280 in the ␣-chain of the GM-CSF-R makes an electrostatic interaction with Asp 112 in the D helix of GM-CSF (33), whereas Glu 21 in the A helix probably interacts with Tyr 365 , His 367 , and Ile 368 of the ␤-common receptor chain (34). IL-4 binding to the IL-4 receptor ␣ chain involves a patch of charged residues on the A and C helices that is likely to interact with charged residues on the receptor (35). In other cases such as the growth hormonereceptor complex, the most important interactions are hydrophobic (36).…”
Section: Discussionmentioning
confidence: 99%
“…9 Direct experiments in the BIAcore system have revealed that the normally glycosylated mIL-4 directly binds to hIL-4 receptor a (Ra). 9 Moreover, several previous reports have shown that hIL-4 is active in mice or rats in vivo in a fashion similar to that of mIL-4. [10][11][12] It is therefore possible that hIL-4 may be at least partially active in vivo in mice.…”
Section: Discussionmentioning
confidence: 99%
“…Many biological processes rely on the rapid formation of protein-ligand complexes (1)(2)(3)(4)(5). Consequently, there has been great interest in elucidating the mechanisms through which binding partners are able to efficiently recognize each other in solution and adopt the correct conformations, relative positions, and orientations to form native stereo-specific complexes.…”
mentioning
confidence: 99%